ANALISIS PENGELOLAAN DANA PREMI PRULINK SYARIAH PADA ASURANSI SYARIAH PT. PRUDENTIAL LIFE ASSURANCE PALEMBANG - Rizki Kusuma Damayanti; Mukhtaruddin Mukhtaruddin; Emylia Yuniartie (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2013)
In general mean, insurance is an agreement of insurer (insurance company) with insured (insurance customers). By accepting premium funds from the insured, insurer promised to pay a number of guarantee when the insured have a failure, damage and loss of some goods, etc. by the insured pay premium funds as much as determined by insurer every months. Progress of insurance in Indonesia currently has improved very significant. According to Association of Syariah Insurance Indonesia/Asosiasi Asuransi Syariah Indonesia (AASI) currently some of insurance company prefer to bulid unit of syariah insurance than to build a new company by focus to the syariah insurance, one of them is PT. Prudential Life Assurance. PT. Prudential Life Assurance offer to build unit of product link both of the conventional and syariah. This research will discuss about Management PRUlink Syariah Premium Funds Analysis on Syariah Insurance in Management PRUlink Syariah Premium Funds Purpose of this research to find out how to Management PRUlink Syariah Premium Funds. Types of this research used by the authors is descriptive and qualitative research method. Data used in this research is primary data and secondary data. Data analysis technic used in this research is descriptive data analysis method, because this research to describe Management Premium Funds mechanism PRUlink Syariah in PT. Prudential Life Assurance.